The inevitable retreat? digital media spaces and marriageability dynamics in modern Black American communities - Green, Mackenzie M. (2018)
The past four decades show significant increase in number of marriages between Black men and non-Black women, and decline in marriage overall for Black women (Crowder and Tolnay 2000; Raley, Sweeney, and Wondra 2015). This retreat from marriage by Black women has been explored focusing on deficits in the number of available partners, but the role of racial intermarriage has been widely ignored. Factors attributed to exchange within Black communities include increase of economic autonomy and higher collective educational attainment of Black women and minimal employment opportunities, mass incarceration, and lower educational attainment of Black men (Crowder and Tolnay 2000; Raley, Sweeney, and Wondra, 2015). While literature supports this change, little has been done to investigate framing images and discourse circulated through digital media spaces. I argue that contemporary patterns of Black American mate-selection are influenced by digital social media entities (re)enforcing negative notions of Black American womanhood, leading Black men to avoid them as romantic partners. The goal of my research is two-fold. First, I propose to utilize digital social media space, namely Instagram, to identify common themes that influence perceptions of beauty, desirability, and the potential of romantic partnerships in young Black American communities. Second, I will discuss social and psychological implications and long-term effects which accompany the shunning of Black American women through digital media spaces. In doing the latter, I investigate historical and modern typecasts ascribed to Black American womanhood, and possible effects of long term negative framing of African Americans (Black women particularly) on the mate selection process. Through this historical analysis I study this phenomenon through a lens of the past, and one of the future to create awareness about historical origin and future implications. I expect that negative ascribed characteristics often depicted in social media are internalized by the community and function to influence the mate selection processes within it. I will discuss implications of heavy social media usage for Black American women especially, and ideas for combatting negative effects on younger Black female generations’ self-esteem and empowerment in writing narratives reflecting true lived experience. My research assumes that without positive ascriptions of Black women or “alternative” narratives from social media entities, future generations of Black Americans will make romantic decisions with a skewed view of themselves and those they choose to select or reject